2003
DOI: 10.1002/anie.200352157
|View full text |Cite
|
Sign up to set email alerts
|

Structures and Solid‐State Dynamics of One‐Dimensional Water Chains Stabilized by Imidazole Channels

Abstract: Proton wires: One‐dimensional water chains play an important role in proton permeation through transmembrane proteins. The X‐ray crystal structures as well as solid‐state 2H and 17O NMR and calorimetry studies of two imidazole hydrates that stabilize infinite one‐dimensional water chains are reported (see picture; N blue, O red, H white). The 2H NMR spectroscopic studies suggest that water molecules in both compounds undergo different reorientational dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(73 citation statements)
references
References 38 publications
(36 reference statements)
1
72
0
Order By: Relevance
“…This way of plotting is commonly used (e.g., in ref. 4) to reflect that one of the two hydrogen atoms in every water molecule is positionally disordered and thus is treated as half-occupancy as pointed out in the text. From the viewpoint of crystallography, these dynamic hydrogen atoms are alternatively hydrogen-bonded to adjacent water molecules in the 1D ice.]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This way of plotting is commonly used (e.g., in ref. 4) to reflect that one of the two hydrogen atoms in every water molecule is positionally disordered and thus is treated as half-occupancy as pointed out in the text. From the viewpoint of crystallography, these dynamic hydrogen atoms are alternatively hydrogen-bonded to adjacent water molecules in the 1D ice.]…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a core-sheath 1D ice structure has been detected in a neutron scattering experiment (5) where the core is a single-file water chain and the sheath is an octagon ice nanotube (provisionally named as 1D ice IVa). Previous classical molecular dynamics simulations (13,14) have suggested that the pentagon and heptagon ice nanotubes are 1D ice with mixed ferroelectric/antiferroelectric domains.Besides the carbon nanotubes, a large number of organic and inorganic species have been successfully synthesized as hosts for confining water on the nanoscale (4,17,(25)(26)(27)(28). Nevertheless, species that can lead to single-phase ferroelectric ice have not been demonstrated experimentally.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[17] The nature of the structural constraints that stabilise 1D water chains has been explored. [18] The 1D water chains bridge the adjacent polymer double chains through O1···O1W [2.764(3) Å], O1W···N11 [2.938(3) Å] and O2W···N14 [2.902(4) Å] hydrogen bonds, to form a double layer structure parallel to the ab plane. Through the extension of the water chains along the c-axis double-layered nets are generated, and these in turn form a 3D supermolecular framework ( Figure S2).…”
Section: Structure Ofmentioning
confidence: 99%